The challenges of commissioning home care for older people in England: commissioners' perspectives. Issue 8 (21st August 2021) - Davies, Karen; Dalgarno, Elizabeth; Davies, Susan; Roberts, Amy; Hughes, Jane; Chester, Helen; Jasper, Rowan; Wilson, David; Challis, David
Abstract: Home care for older people in England is commissioned through local authorities working predominantly with independent providers of care. Commissioners operate in a market model, planning and procuring home care services for local populations. Their role involves 'managing' and 'shaping' the market to ensure an adequate supply of care providers. Another imperative, emerging from the principles of personalisation, is the drive to achieve user outcomes rather than 'time and task' objectives. Little formal research has investigated the way commissioners reconcile these different requirements and organise commissioning. This study investigated commissioning approaches using qualitative telephone interviews with ten commissioners from different local authorities in England. The characteristics of commissioning were analysed thematically. Findings indicated (a) commissioning involved complex systems and processes, uniquely shaped for the local context, but frequently changed, suggesting a constant need for reframing commissioning arrangements; (b) partnerships with providers were mainly transactional, with occasional examples of collaborative models, that were considered to facilitate flexible services more appropriate for commissioning for personalised outcomes; and (c) only a small number of commissioners had attempted to reconcile the competing and incompatible goals of tightly prescribed contracting and working collaboratively with providers. A better understanding of flexible contracting arrangements and the hallmarks of a trusting collaboration is required to move beyond the procedural elements of contracting and commissioning.